Measuring employment in the agri-food system: Existing data and directions for future research - Ambler, Kate; Herskowitz, Sylvan; Labarta, Ricardo; Scollard, Phoebe; Maredia, Mywish K. (International Food Policy Research Institute, 2019)
Rapidly growing populations in sub-Saharan Africa have resulted in a focus by both policy-makers and researchers on understanding and creating employment opportunities for youth. While most attention has focused on jobs outside the agricultural sector, the persistent importance of agriculture in African economies means that the sector cannot be ignored when considering new employment opportunities. A large portion of existing work has made use of Living Standard Measurement Surveys (LSMS) and oth-ers of similar structure and design to describe employment patterns, by focusing on the distinction be-tween on- and off-farm labor, and household enterprises versus hired or wage labor.